Viral Entanglements: Bodies, Belonging and Truth‐claims in Health Borderlands. (17th January 2022) - Kasstan, Ben
Abstract: This article contributes to anthropological debates surrounding borderlands and biosecurity by tracing the multiple pursuits of protection that emerge between the state and minorities during infectious disease outbreaks. Drawing on an ethnographic study of child health in Jerusalem following epidemics of measles and COVID‐19, the article demonstrates how responses to public health interventions are less about compliance or indiscipline than a competing pursuit of immunity to preserve religious lifeworlds. The voices of Orthodox Jews are situated alongside printed broadsides that circulated anonymous truth‐claims in Jerusalem neighborhoods. These broadsides cast state intervention against historical narratives of deception and ethical failures. Borderland tensions, like a virus, mutate and influence responses to authority and biosecurity, and they reconfigure vernacular entanglements of religion, state, and health. The article encourages anthropologists to consider responses to public health interventions and non‐vaccination beyond a COVID‐19 silo, as part of situated relations between states and minority populations.